The Employment Status of Young Adult Black Males Residing in Poverty Households: Recent Milwaukee County Experience - (:unkn) unknown (My University, 1992)
Harold Rose, UWM professor of Geography and Urban Studies, examined the findings of the Employment and Training Institute analysis of employment held by 8,479 young African American males from Wisconsin families seeking or receiving public assistance (AFDC, food stamps, and/or medical assistance) in 1987-1989. Rose discusses the findings in light of a wide variety of perspectives by drawing on national literature addressing social and economic changes in the 1980s, welfare dependency, conditions in inner city Milwaukee, labor force participation rates, extended presence of young black males in parental households, employment sectors, subpopulations’ earnings history, attachment to the labor force, school enrollment and attainment, persistence in the workforce, job growth in the local economy, spatial mismatch between job openings and job seekers, black youth styles and employment prospects, the role of the residential environment on the group’s world view, concentrated poverty and the quality of neighborhood life, recent growth of concentrated poverty neighborhoods, intensification of ghetto poverty, dispersion of low income households, zones of black neighborhood expansion, and behavioral norms in core zones. Rose observes, “The parents of this cohort, who grew up in this community, or arrived from elsewhere during the turbulent 1960s, must by now be questioning the hand they drew. Given the promise associated with that decade, the screens of opportunity turned out to be much finer than was anticipated, especially for males growing up in poor households.”
Keywords: African Americans; youth employment; race discrimination